In-Vitro Antioxidant and Cytotoxicity Screening of Different Bark Extracts of Aegle Marmelos L - Kaise Hamid, Farhana Diba, Kaniz Fatima Urmi, Muhammad Erfan Uddin, Fatema Tuz Zohera, Md. Razibul Habib (Journal of Applied Pharmaceutical Science)
The present study was designed to investigate the antioxidant and cytotoxic activity of the methanol, ethyl acetate and n-hexane extracts of bark of Aegle marmelos. The antioxidant properties was assessed by using 1, 1-diphenyl-2- picrylhydrazyl radical (DPPH) and Nitric Oxide (NO) scavenging capacity. The methanolic, ethyl acetate and n-hexane bark extracts ofAegle marmelos showed potential DPPH free radical scavenging activity having IC50 values of 37.056 Î¼g/ml, 43.379 Î¼g/ml and 66.180 Î¼g/ml respectively compared with the IC50 value of Ascorbic acid 33.447 Î¼g/ml. The Ethyl acetate extract of Aegle marmelos displayed excellent antioxidant activity in nitric oxide (NO) scavenging capacity assay with IC50 value of 28.377 Î¼g/ml compared with the standard ascorbic acid, IC50 value of 22.175 Î¼g/ml. The cytotoxicity assay was performed by applying brine shrimp lethality bioassay method. Among all the fractions, n-hexane extract shown profound cytotoxic activity with LC50 value of 4.482 Î¼g/ml that was followed by methanolic and ethyl acetate having LC50 values of 5.278 and 5.278 Î¼g/ml respectively in comparison with the standard vincristine sulfate with LC50 value of 3.364 Î¼g/ml. The findings of the present study suggest that the extracts from Aegle marmelos bark have potential cytotoxicity and antioxidant effects.
Keywords: Aegle marmelos,Cytotoxicity,DPPH,Antioxidant,Scavenging.